Tetracrystalline Tetrablock Quarterpolymers: Four Different Crystallites under the Same Roof - Ladelta, Viko; Zapsas, George; Abou‐hamad, Edy; Gnanou, Yves; Hadjichristidis, Nikos (Angewandte Chemie International Edition, 2019)
Multicrystalline block polymers having three or more crystalline segments are essential materials for the advancement of physics in the field of crystallinity. The challenging synthesis of multicrystalline polymers has resulted in only a limited number of tricrystalline terpolymers having been reported to date. We report, for the first time, the synthesis of polyethylene‐b‐poly(ethylene oxide)‐b‐poly(ϵ‐caprolactone)‐b‐poly(l‐lactide) (PE‐b‐PEO‐b‐PCL‐b‐PLLA), a tetracrystalline tetrablock quarterpolymer, by combining polyhomologation, ring‐opening polymerization, and an organic/metal “catalyst switch” strategy. 1H NMR spectroscopy and gel‐permeation chromatography confirmed the formation of the tetrablock quarterpolymer, while differential scanning calorimetry, X‐ray diffraction, and wide‐line separation solid‐state NMR spectroscopy revealed the existence of four different crystalline domains. Four in a row: The combination of polyhomologation, ring‐opening polymerization, and an organic/metal catalyst switch strategy led to the tetracrystalline tetrablock quarterpolymer polyethylene‐b‐poly(ethylene oxide)‐b‐poly(ϵ‐caprolactone)‐b‐poly(l‐lactide). The existence of four different crystalline domains in the polymer was confirmed by differential scanning calorimetry, X‐ray diffraction, and wide‐line separation solid‐state NMR spectroscopy.